Reply to: Towards solving the missing ice problem and the importance of rigorous model data comparisons - Gowan, Evan J; Zhang, Xu; Khosravi, Sara; Rovere, Alessio; Stocchi, Paolo; Hughes, Anna L C; Gyllencreutz, Richard; Mangerud, Jan; Svendsen, John-Inge; Lohmann, Gerrit (Nature Communications, 2022)
Our recent ice sheet reconstruction, PaleoMIST 1.0, was created on the basis of using near-field (i.e., ice sheet proximal) geological constraints. This was done so that it would be independent of far-field relative sea level observations, that are subject to uncertainties in the global distribution of ice, and deep sea proxy based global mean sea level reconstructions, which have large uncertainties due to temperature and salinity effects. We do not disagree with the interpretation of the far-field data highlighted by Yokoyama et al., but emphasise that near-field constraints should be the starting point for reconstructing ice sheets.